Analisis Kelayalan Bisnis pada UMKM Royal Steak di Salatiga - Jumiatun; Era Zaher Afrilida; Adinda Ayu Sukmawati; Trenada rida Maharani; Siti Tasyfiah; Roni Ainur Rofiq; Reymon Putra Saroni Zaluku (Jurnal Inovasi Bisnis Manajemen dan Akuntansi, 2026)
This study aims to analyze the business feasibility of Royal Steak, a western food culinary business specializing in Chicken Bar & Steak in Salatiga City. The primary objective of this research is to comprehensively evaluate the business potential from various aspects in order to support sustainable business growth. This study employs a mixed-methods approach, combining qualitative and quantitative methods. Data were collected through direct observation, customer review analysis, and monitoring of the business's social media platforms. The analysis covers six main aspects: legal, market and marketing, management and human resources, technical and technological, environmental, and financial. The results indicate that Royal Steak is feasible to operate, as it demonstrates strong competitiveness through consistent product quality, affordable prices targeting students and families, and a strategic location in the center of Salatiga City. Nevertheless, several weaknesses still need to be addressed, including incomplete business legality, non-digitalized financial records, and the absence of integrated food delivery services through digital platforms. Therefore, the study recommends completing the required legal documents, modernizing the financial management system, integrating food delivery platforms, and developing menu innovations and marketing strategies. This research highlights the importance of conducting a business feasibility study as a strategic guideline for establishing, managing, and developing a business in an increasingly competitive business environment.